Knowledge, attitude, and behavior of pregnant women on early initiation of breastfeeding - Yoke Ayukarningsih; Sutedja Sutedja; Anna Mardiyah (Indonesian Pediatric Society, 2014)
Background Infant mortality rate is an indicator of the degree ofhealth in society. In Indonesia, the infant mortality rate remainshigh, with most deaths occurring in the first 24 hours of life.Breastfeeding has been shown to reduce infant mortality, especiallyif undertaken in the first hour of life. This practice is knownas early initiation of breastfeeding (EIB). According to variousstudies, EIB implementation may be influen ced by many factorssuch as knowledge, attitude, behavior, and health care facilities.Objective To assess the level of knowledge, attitude, and behaviorof pregnant women towards EIB.Methods We conducted a descriptive study using questionnaireson 74 pregnant women in the outpatient clinic of Obstetrics andGynecology Department, Dustira Hospital, Cimahi, West Java,Indonesia from November to December 2012.Results Out of 74 respondents, 21 % had a good level of knowledgeon EIB, 23% had an adequate knowledge, and 56% had less thanadequate knowledge on EIB. A positive attitude towards EIBwas found in 65% of the respondents, while 35% had a negativeattitude. With regards to behavior conducive to EIB, 8% ofrespondents had good behavior, 57% had moderate behaviot; and35%had less than adequate behavior.Conclusion Majority of pregnant women have less than adequateknowledge on EIB, a positive attitude towards EIB, and moderateto less than adequate behavior conducive to EIB.